2020
DOI: 10.1038/s41598-020-73362-z
|View full text |Cite
|
Sign up to set email alerts
|

Early neurotransmission impairment in non-invasive Alzheimer Disease detection

Abstract: Alzheimer Disease (AD) is a pathology suffered by millions of people worldwide and it has a great social and economic impact. Previous studies reported a relationship between alterations in different amino acids and derivatives involved in neurotransmission systems and cognitive impairment. Therefore, in this study the neurotransmission impairment associated to early AD has been evaluated. For this purpose, different amino acids and derivatives were determined in saliva samples from AD patients and healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
(48 reference statements)
1
7
0
1
Order By: Relevance
“…On the contrary, ACh levels in the submandibular gland from AD patients were found higher compared with control subjects (p < 0.05; Figure 4B ), in agreement with previously reported data in saliva ( 33 ). These findings may be explained by the use of acetylcholinesterase (AChE) inhibitors in the treatment of AD, which may help to increase and prolong the activity period of the released Ach.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, ACh levels in the submandibular gland from AD patients were found higher compared with control subjects (p < 0.05; Figure 4B ), in agreement with previously reported data in saliva ( 33 ). These findings may be explained by the use of acetylcholinesterase (AChE) inhibitors in the treatment of AD, which may help to increase and prolong the activity period of the released Ach.…”
Section: Resultssupporting
confidence: 93%
“…In agreement with this, AChE activity was found significantly lower in AD patients compared with healthy control age-matched subjects ( 34 ). Moreover, a recent study showed higher levels of ACh in saliva from AD patients ( 33 ). In our present study, 13 out of 15 AD patients were under AchE inhibitor treatment, which could explain the higher Ach levels observed in their submandibular glands.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1,2 ] Suitable methods used to diagnose an individual's predisposition toward neurological degeneration and dementia‐associated disorders through early biomarkers can bridge this gap. [ 3–5 ] The worldwide social and economic impact of Alzheimer's disease (AD) dictates the need for the timely invention of theranostics (therapeutics + diagnostics) for this disease. Continuous failure of anti‐AD drugs targeted to neurotransmitters and their interactions with toxic amyloid‐β (Aβ) peptides in clinical trials has brought the spotlight back to amyloidosis in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a multivariate analysis including sensitivity, specificity and area under the curve (AUC) revealed a few promising indices for creatine, acetylcholine, glutamine and myo-inositol. These neurotransmitters could be used as promising non-invasive biomarkers for diagnosing AD and cognitive impairment [ 57 ].…”
Section: Biomarkers In the Diagnosis Of Alzheimer’s Diseasementioning
confidence: 99%